Critical thinking of repositioning practice as a quality of nursing care indicator - Abdulkareem S. Iblasi; Yupin Aungsuroch; I Gede Juanamasta; Jintana Yunibhand; I Wayan Suardana (Faculty of Nursing Universitas Padjadjaran, 2024)
Repositioning is all nursing activities that aim to change the posture of bedridden patients from one side to another during the hospital stay to minimize the pressure load on bony prominences and prevent pressure ulcers or injuries from developing. This is a discussion paper based on nursing and healthcare quality literature references. This paper describes the importance of repositioning practice based on the empirical study and experience as nurses and nurse managers. This perspective supports the existing literature to link repositioning practice and the quality of nursing care process indicators. Repositioning practice could be considered as an indicator of the process of care. This paper emphasizes repositioning practice as a fundamental nursing intervention and how it becomes meaningful for nursing indicators. Nurses need a standard of repositioning and its measurement at the international level.